2018
DOI: 10.9734/ajpas/2018/v1i424552
|View full text |Cite
|
Sign up to set email alerts
|

On the Properties and Applications of Transmuted Odd Generalized Exponential-Exponential Distribution

Abstract: This article proposed a new distribution referred to as the transmuted odd generalized exponential-exponential distribution (TOGEED) as an extension of the popular odd generalized exponential- exponential distribution by using the Quadratic rank transmutation map (QRTM) proposed and studied by [1]. Using the transmutation map, we defined the probability density function (pdf) and cumulative distribution function (cdf) of the transmuted odd generalized Exponential- Exponential distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…The result is an affirmation to the fact that the method quadratic rank transmutation map for adding a single or transmuted parameter has increased the flexibility of the power Gompertz distribution. Hence, this study is in line with the conclusions in [33,36,37,38,39,40,49,50,51].…”
Section: Data Set Isupporting
confidence: 92%
See 1 more Smart Citation
“…The result is an affirmation to the fact that the method quadratic rank transmutation map for adding a single or transmuted parameter has increased the flexibility of the power Gompertz distribution. Hence, this study is in line with the conclusions in [33,36,37,38,39,40,49,50,51].…”
Section: Data Set Isupporting
confidence: 92%
“…It has been discovered that using the quadratic rank transmutation map by [8] brings about more skewed and flexible probability distributions with an additional shape parameter usually known as the transmuted parameter and this process has led to many flexible compound distributions such as the Transmuted Gompertz distribution [33], the transmuted exponential Lomax distribution by [36], the transmuted odd generalized exponential exponential distribution [37], the transmuted Weibull-Exponetial distribution [38], the transmuted Lindley-Exponential distribution [39] and the transmuted Weibull-Rayleigh distribution [40].…”
Section: Introductionmentioning
confidence: 99%
“…Dataset: This data represents the remission times (in months) of a random sample of 128 bladder cancer patients adopted from the work of Rady et al [36]. It has previously been used by Lee and Wang [40], Rady et al [36], Ieren and Chukwu [41] and Abdullahi et al [42]. It is given and summarized as follows: 0.080, 0.200, 0.400, 0.500, 0.510, 0.810, 0.900, 1.050, 1.190…”
Section: Applications To Three Real Life Datasetsmentioning
confidence: 99%
“…This data set represents the remission times (in months) of a random sample of 128 bladder cancer patients. It has previously been used in [21,22,23]. It is summarized as follows: From the descriptive statistics in Table 1, it is observed that the data set is positively skewed with a very high coefficient of kurtosis and therefore suitable for flexible and skewed distributions.…”
Section: Data Setmentioning
confidence: 99%